2002
DOI: 10.1029/2000jd000192
|View full text |Cite
|
Sign up to set email alerts
|

Optical closure for an aerosol column: Method, accuracy, and inferable properties applied to a biomass‐burning aerosol and its radiative forcing

Abstract: [1] During the Lindenberg Aerosol Characterization Experiment (LACE 98), airborne measurements of aerosol size distribution, fine-particle concentration, particle absorption coefficient, backscatter coefficient, depolarization, and chemical composition as well as ground-based measurements of spectral particle optical depth and of spectral backscatter and extinction coefficients were performed in the aerosol column above Lindenberg, Germany. We compare the measured optical parameters with calculations from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
124
1
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(141 citation statements)
references
References 36 publications
(56 reference statements)
12
124
1
1
Order By: Relevance
“…Additionally, lidar ratios are larger for larger particles. Lidar observations of an aged biomass-burning plume that had originated from western Canada in 1998 and which was observed over Germany during the Lindenberg Aerosol Characterization Experiment (LACE) 98 showed that theÅngström exponent was as small as 0.06 which indicates well-aged smoke particles even larger than the ones found in this study (Fiebig et al, 2002;. Dual-wavelength Raman lidar observations of Siberian forest fire smoke were carried .…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, lidar ratios are larger for larger particles. Lidar observations of an aged biomass-burning plume that had originated from western Canada in 1998 and which was observed over Germany during the Lindenberg Aerosol Characterization Experiment (LACE) 98 showed that theÅngström exponent was as small as 0.06 which indicates well-aged smoke particles even larger than the ones found in this study (Fiebig et al, 2002;. Dual-wavelength Raman lidar observations of Siberian forest fire smoke were carried .…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that the particle size was larger and the non-sphericity was lower. The optical characteristics of forest-fire smoke in the troposphere were reported in previous works Fiebig et al 2002;Mattis et al 2003;Murayama et al 2004;Amiridis et al 2009). Murayama et al (2004) reported an S 1 of 65 sr at 532 nm, and a PDR of 0.06 for a Siberian smoke plume at altitudes of 3.2 to 3.8 km.…”
Section: Discussionmentioning
confidence: 99%
“…Lidar backscatter profiles (Forster et al, 2001;Fiebig et al, 2002;Wandinger et al, 2002) show this aerosol layer to consist of two sub-layers from 3.8-4.3 km and 4.7-5.2 km above sea level (ASL) on 9 August, 1998. Backward trajectory calculations Forster et al, 2001) as well as aerosol index data obtained by the Total Ozone Mapping Spectrometer (TOMS) on the Earth Probe satellite Hsu et al, 1999) as well as model tracer studies (Forster et al, 2001) relate the aerosol layer to forest fires in northern Canada near Great Bear Lake, Northwest Territories.…”
Section: The Lace 98 Forest Fire Aerosol Casementioning
confidence: 99%
“…The influence of plume dilution receives special attention. The studied case, a plume of aerosol emitted by forest fires in Northern Canada in 1998, has been the subject of several previous works (Hsu et al, 1999;Fromm et al, 2000;Forster et al, 2001;Fiebig et al, 2002;Formenti et al, 2002a) whose results are summarised. The particle size distribution in the plume as measured over Lindenberg, Germany, during the Lindenberg Aerosol Characterisation c European Geosciences Union 2003 882 M. Fiebig et al: Radiative forcing of forest fire aerosol Experiment (LACE 98) on 9 August 1998 is classified by briefly reviewing other measurements in such plumes, emphasizing the temporal evolution of the particle size distribution.…”
Section: Introductionmentioning
confidence: 99%